Effector T cell chemokine IP-10 predicts cardiac recovery and clinical outcomes post-myocardial infarction - Sopova, Kateryna; Tual-Chalot, Simon; Müller-Hennessen, Matthias; Vlachogiannis, Nikolaos I.; Georgiopoulos, Georgios; Biener, Moritz; Sachse, Marco; Turchinovich, Andrey; Polycarpou-Schwarz, Maria; Spray, Luke; Maneta, Eleni; Bennaceur, Karim; et al. (Frontiers in immunology, 2023)
Background and aimsPreclinical data suggest that activation of the adaptive immune system is critical for myocardial repair processes in acute myocardial infarction. The aim of the present study was to determine the clinical value of baseline effector T cell chemokine IP-10 blood levels in the acute phase of ST-segment elevation myocardial infarction (STEMI) for the prediction of the left ventricular function changes and cardiovascular outcomes after STEMI.MethodsSerum IP-10 levels were retrospectively quantified in two independent cohorts of STEMI patients undergoing primary percutaneous coronary intervention.ResultsWe report a biphasic response of the effector T cell trafficking chemokine IP-10 characterized by an initial increase of its serum levels in the acute phase of STEMI followed by a rapid reduction at 90min post reperfusion. Patients at the highest IP-10 tertile presented also with more CD4 effector memory T cells (CD4 TEM cells), but not other T cell subtypes, in blood. In the Newcastle cohort (n=47), patients in the highest IP-10 tertile or CD4 TEM cells at admission exhibited an improved cardiac systolic function 12 weeks after STEMI compared to patients in the lowest IP-10 tertile. In the Heidelberg cohort (n=331), STEMI patients were followed for a median of 540 days for major adverse cardiovascular events (MACE). Patients presenting with higher serum IP-10 levels at admission had a lower risk for MACE after adjustment for traditional risk factors, CRP and high-sensitivity troponin-T levels (highest vs. rest quarters: HR [95% CI]=0.420 [0.218-0.808]).ConclusionIncreased serum levels of IP-10 in the acute phase of STEMI predict a better recovery in cardiac systolic function and less adverse events in patients after STEMI.
Gesehen am 25.09.2023